Digital project solutions for business and hospitality industry: Modern challenges for the personnel - Shestakova, Anna; Vikarchuk, Olga; Belogor, Lyudmila (Global Prosperity, 2023)
The importance of establishing the role of digital project solutions using the example of the agribusiness and the hospitality industry is shown particularly for professionals with experience in the field of information technology and agriculture. The aspects of the recruitment process and further employment in the agricultural sector, considering the rapid spread of digitalization, are outlined in the article. The generalized order of the methods for initial assessment of the recruitment process for the agricultural enterprises is described with an emphasis on digital skills. The proportion of households with access to the Internet in urban and rural areas is examined. The main HR trends are identified, among which digitalization and the use of e-platforms are the most prominent. It is established that e-platforms have various applications, such as communication between agricultural holdings and agricultural enterprises as well as search, lease or sale of the land lots, agricultural consulting, etc. The examples of electronic platforms and digital services in the agricultural sector as well as the specifics of their use are considered in the article. The main challenges of digital transformation of agricultural areas and rural labor potential are analyzed. It is concluded that digitalization can pose additional challenges for small farmers and large agricultural holdings, which require strengthening the strategic policy development in production and personnel management through the effective use of digital solutions.